Enhanced Recovery Protocol Decreases Postoperative Opioid Use after Penile Inversion Vaginoplasty - Maria V. Rios Sanchez, MPH; Nicole Sanchez Figueroa, MD; Eugene Zheng, MD; Dan Sotelo Leon, MD; Jorys Martinez-Jorge, MD; Vahe Fahradyan, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Penile inversion vaginoplasty (PIV) entails considerable soft-tissue dissection to the perineal region and involves complex tissue rearrangement. This study examines the role of an enhanced recovery after surgery (ERAS) pathway after PIV in reducing opioid use and controlling postoperative pain. Methods:. A retrospective study of 50 transfemale patients who underwent PIV at a single institution from June 2021 to January 2023 was completed. The study compared 2 groups of patients who were given different postoperative pain management regimens: group A received standard postoperative analgesics and group B received ERAS. Variables such as postoperative pain scores on the numeric pain rating scale (0–10), use of opioid medication, length of hospital stay, and patient comorbidities were recorded and compared across the 2 groups. Results:. The average hospital stay length was 4.92 (±0.85) days. Group A had a slightly longer average stay compared with group B. The average pain level in both groups was 4.25 (SD ±1.51). Group A exhibited a slightly higher average pain level of 4.31 (±1.53), whereas group B exhibited 4.16 (SD±1.51) (P = 0.77). Although pain levels did not significantly vary between the 2 groups, there was a statistically significant decrease in the amount of opioid medication used in group B with a P value of 0.009. Conclusions:. ERAS protocol is effective in decreasing opioid usage in the immediate postoperative setting after PIV.